2021
DOI: 10.3748/wjg.v27.i44.7582
|View full text |Cite
|
Sign up to set email alerts
|

Orexins: A promising target to digestive cancers, inflammation, obesity and metabolism dysfunctions

Abstract: Hypothalamic neuropeptides named hypocretin/orexins which were identified in 1998 regulate critical functions such as wakefulness in the central nervous system. These past 20 years had revealed that orexins/receptors system was also present in the peripheral nervous system where they participated to the regulation of multiple functions including blood pressure regulation, intestinal motility, hormone secretion, lipolyze and reproduction functions. Associated to these peripheral functions, it was found that ore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 112 publications
(167 reference statements)
0
22
0
Order By: Relevance
“…Since several years, our group demonstrated that orexin receptor type 1 (OX1R) but not orexin receptor type 2 (OX2R) was expressed in digestive cancer cells including pancreatic, colon, and liver cancers ( 14 ) where its activation by orexins induced a mitochondrial apoptosis leading to anti-tumoral impact of orexin/OX1R system ( 15 ). Orexins specifically activated two receptor subtypes belonging to the G-protein-coupled receptor (GPCR) family ( 16 ). Orexins, encompassing two isoforms named orexin-A (OxA) and orexin-B (OxB), are hypothalamic neuropeptides produced by the same precursor, the prepro-orexin ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since several years, our group demonstrated that orexin receptor type 1 (OX1R) but not orexin receptor type 2 (OX2R) was expressed in digestive cancer cells including pancreatic, colon, and liver cancers ( 14 ) where its activation by orexins induced a mitochondrial apoptosis leading to anti-tumoral impact of orexin/OX1R system ( 15 ). Orexins specifically activated two receptor subtypes belonging to the G-protein-coupled receptor (GPCR) family ( 16 ). Orexins, encompassing two isoforms named orexin-A (OxA) and orexin-B (OxB), are hypothalamic neuropeptides produced by the same precursor, the prepro-orexin ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Orexins specifically activated two receptor subtypes belonging to the G-protein-coupled receptor (GPCR) family ( 16 ). Orexins, encompassing two isoforms named orexin-A (OxA) and orexin-B (OxB), are hypothalamic neuropeptides produced by the same precursor, the prepro-orexin ( 16 ). The main biological function of orexins was to control the wakefulness ( 17 ), and a dysregulation of this function led to human narcolepsy type I pathology ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…The effect of CRF is cancer-type specific: CRF binding to the CRF receptor can potentiate an anti-tumor response in endometrial cancer 45 and promote cancer progression in colon cancer 46 or breast cancer for instance 41 . Orexin receptors are expressed in gastric cancer (including esophageal cancer) and treatment with orexin has been shown to induce apoptosis in colorectal, neuroblastoma and pancreatic cancer cells 43 . Orexin A was even able to induce apoptosis in drug resistant colorectal cancer cell lines 47 .…”
Section: Resultsmentioning
confidence: 99%
“…In particular, the Corticotropin Releasing Hormone (CRH) signaling pathway and the orexin receptor pathway were upregulated in a subspace of the ESCC latent space. These pathways have been previously shown to be overexpressed in several cancers and can be used for targeted therapy [41][42][43][44] .…”
Section: Cansig Rediscovers Previously Investigated Signatures In Thr...mentioning
confidence: 99%
“…Beyond these CNS actions, orexins and their receptors had biological impacts in peripheral nervous system (PNS). Although less investigated, the role of orexin in PNS ( Figure 1 ) revealed actions on neuroendocrine functions, blood pressure, metabolism, reproductive functions, energy balance and gastrointestinal motility ( 13 ).…”
Section: Introductionmentioning
confidence: 99%